شکستی سیستەمی سیاسی لە عێراق دوای ساڵی ٢٠٠٣ (توێژینەوەی هەڵێنجراو) - قادر, سەردار محێدین; مەولود, پەخشان عبدالرحمن (Sulaimani Journal for Humanities, 2023)
Abstract: After 2003, there was a huge security gap due to the disappearance of state control. Iraq's political system was becoming increasingly fragile in terms of stability and security. This made Iraq as a state to back off from its responsibilities for fulfilling a number of duties. In this study, we have tried to answer our main research question regarding what were the signs of Iraq's failure after 2003, and what were the reasons behind this failure. For this purpose, we have used number of sources and data collection methods in three languages: Kurdish, Arabic and English. This study found that Iraq's political system has failed according to all political, security, economic and social indicators. This has plunged the country into a number of crises. There were number of reasons behind this failure, especially internal and external factors, such as occupation, external intervention, ethnic and sectarian conflicts, terrorism and corruption. All of mentioned reasons have taken Iraq's political system to a dangerous stage. The accumulation of these problems were an expected failure for post 2003 Iraq's political system.
Keywords: Iraq; political system; failed state; external interference; corruption